PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MINAT SISWA BARU UNTUK MELANJUTKAN PENDIDIKAN DI SMAK ST. PETRUS KEWAPANTE - TAUFIQ; AMIR DJONO; NURDIN H. ABD RAHMAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to find the effect of leadership on the interest of new students to continue their education at SMAK St. Peter Kewapante. This research was conducted at St. High School. Petrus Kewapante Maumere in 2021. The population in this study were all students of class X in 2021. The sample in this study amounted to 51 people. The sampling technique used is probability sampling technique by taking samples from each member of the population, given the Bsame opportunity to be selected as a sample. This study uses a quantitative descriptive approach. All statements are valid, reliable, normal, homogeneous, linear and non-heteroscedastic. Based on the results of simple linear regression calculations obtained leadership = 21.378 + 0.208 products. Hypothesis testing of the results of the t-test calculation results obtained tcount > ttable (3,016 > 2.00), which means H0 is rejected and H1 is accepted. The results show that the coefficient of determination (R Square) of the independent variable on the dependent variable is R2 = 0.142 or 14.2%. So, the results of this study concluded that there is a relationship between the Principal's Leadership on the Interest of New Students to continue their education at SMAK St. Peter Kewapante.